2000
DOI: 10.1007/s002030000163
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids of an Antarctic psychrotolerant bacterium, Sphingobacterium antarcticus, and a mesophilic bacterium, Sphingobacterium multivorum

Abstract: The major carotenoid pigments of an Antarctic psychrotolerant bacterium, Sphingobacterium antarcticus, and a mesophilic bacterium, Sphingobacterium multivorum, were identified as zeaxanthin, beta-cryptoxanthin, and beta-carotene. Analysis was based on ultraviolet-visible spectroscopy, mass spectroscopy, and reversed-phase HPLC. Photoacoustic spectroscopy of intact bacterial cells revealed that the bulk of the pigments in S. antarcticus and S. multivorum was associated with the cell membrane. In vitro studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 36 publications
2
77
1
Order By: Relevance
“…Since these membrane modulations were reported for close relatives in both groups, one can speculate that additional factors contributed to the different response to freeze-thaw cycles. It has been demonstrated that lower cultivation temperatures promoted an increased carotenoid production in psychrotolerant bacteria (Jagannadham et al, 2000). Similarly, Yokoyama et al (1996) reported that bacteria growing under extreme conditions (e.g.…”
Section: Freeze-thaw Cyclesmentioning
confidence: 92%
See 2 more Smart Citations
“…Since these membrane modulations were reported for close relatives in both groups, one can speculate that additional factors contributed to the different response to freeze-thaw cycles. It has been demonstrated that lower cultivation temperatures promoted an increased carotenoid production in psychrotolerant bacteria (Jagannadham et al, 2000). Similarly, Yokoyama et al (1996) reported that bacteria growing under extreme conditions (e.g.…”
Section: Freeze-thaw Cyclesmentioning
confidence: 92%
“…These strategies allow nutrient exchange and enzyme activity to occur, and most importantly prevent intracellular ice nucleation. Recent studies have suggested that pigments such as carotenoids may play a role in the modulation of membrane fluidity in bacteria (Jagannadham et al, 2000). Jagannadham et al (2000) speculated that when cells grow at low temperatures (5 uC), the unsaturated and branched-chain fatty acids increase the fluidity of the membrane, whereas polar carotenoids counterbalance this effect by stabilizing the membrane.…”
Section: Freeze-thaw Cyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the modulation of membrane fluidity is brought about by changing the levels of polar and non-polar carotenoids (Jagannadham and others 2000). Thus, it seems that the pigments interacting with cell membranes increase its rigidity and enable cold-adaptation in cryoconite environment.…”
Section: Discussionmentioning
confidence: 99%
“…Growth at low temperatures can lead to changes in membrane composition (4,23) that could affect the type and density of functional groups present on the cell surface. In addition to changes in fatty acid composition and carotenoid content, Corsaro et al (12) observed an increase in phosphorylation of lipooligosaccharides and exopolysaccharides with an increase in growth temperature for Pseudoalteromonas haloplanktis, an Antarctic bacterium.…”
Section: Downloaded Frommentioning
confidence: 99%